2016
DOI: 10.1007/s12035-015-9673-5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating the Expression of Survivin-HBXIP Complex Contributes to the Protective Role of IMM-H004 in Transient Global Cerebral Ischemia/Reperfusion

Abstract: IMM-H004, a 3-piperazinylcoumarin compound derived from coumarin, has been proved effective against CA1 cell loss and spatial learning impairments resulting from transient global ischemia/reperfusion (TGCI/R), while the mechanism is still largely unknown. Here, we confirmed that treatment of rats with IMM-H004 immediately after TGCI/R ameliorated delayed neuronal death (DND) in the CA1 of hippocampus and cortex. Further study suggested that IMM-H004 contributed to the expression of antiapoptotic protein surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…PC12 cell culture and OGD/R Rat pheochromocytoma PC12 cells were obtained from Peking Union Medical College. The OGD/R was performed as previously described [34]. In brief, PC12 cells were cultured in DMEM with 10% fetal bovine serum, 5% embryonic stem, 100 U/mL penicillin, and 100 U/mL streptomycin at 37°C under a humidified atmosphere containing 5% CO 2 .…”
Section: Reagentsmentioning
confidence: 99%
“…PC12 cell culture and OGD/R Rat pheochromocytoma PC12 cells were obtained from Peking Union Medical College. The OGD/R was performed as previously described [34]. In brief, PC12 cells were cultured in DMEM with 10% fetal bovine serum, 5% embryonic stem, 100 U/mL penicillin, and 100 U/mL streptomycin at 37°C under a humidified atmosphere containing 5% CO 2 .…”
Section: Reagentsmentioning
confidence: 99%
“…When cerebral ischemia develops at the reperfusion stage, the compensation provided by pre-existing nerve cells in the ischemic and hypoxic brain tissues rises abruptly, and is accompanied by a dramatic increase in free radicals that mediate oxidative damage in the affected areas [22,23]. As an end product of oxidation, MDA further aggravates any damage to cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…To explain, pyramidal neurons of the CA1 hippocampal area are particularly sensitive to ischemia, and their apoptosis is an outcome of transient GCI [20]. Therefore, memory deficit is one of the outcomes of transient GCI [5], as in the study carried out by Movassaghi et al who found that exposure of rats to BCCAO could impair spatial memory [21]. To evaluate learning and memory, MWM was used.…”
Section: Discussionmentioning
confidence: 99%
“…reduces brain blood flow [4]. TGCI mediates neuronal cell death resulting in severe neurological and neurobehavioral dysfunction [5]. Among various areas in brain, neurons of CA1 hippocampal area are highly vulnerable to ischemia [6] so that apoptosis of these neurons is an important phenomenon of brain ischemia/reperfusion injury [7].…”
mentioning
confidence: 99%